Effectiveness of ICT Teaching Approach in Education Sector - Arulmurugan, R. (INDIAN EDUCATIONAL REVIEW, 2022)
The proposed article is to describe the various innovative approaches to the teaching-learning process using the Information Communication Technology (ICT) tool. The problems of the conventional teaching approach are identification of the students’ learning level, improvement of critical thinking and interpersonal skills. The prime objective of this article is to establish how it can be overcomed by ICT tools-based learning approach. This article describes various innovative ICT approach methods used to enhance the students’ learning outcome, assessing level of students’ thinking, etc. The article describes the poll-based learning approach, automatic grade generated approach, mind-map approach, online quiz approach, virtual laboratory approach and brainstorm approach. This approach is used not only to identify students’ level but also to generate the student’s grade sheet, individual communication and maintain the assessment documents in a friendly manner.